Intergenerational financial transfers and physical health of old people in rural China: evidence from CHARLS data - Chen,Guangyan (2020)
ABSTRACT: With the reduction of intergenerational temporal transfers, financial transfers from adult offspring to their elderly parents are prevailing in rural China. Although much has been done, little is known about the association between the expansion of intergenerational transfers and rural old people’s physical health in China. The purpose of this paper was to examine the effect of intergenerational financial transfers on the elders’ physical health in rural China. Using data collected from China Health and Retirement Longitudinal Study (CHARLS), panel data fixed effect model and threshold model are employed to estimate the impact of intergenerational financial transfers on the old people’s physical health in rural areas. Results showed that; although, the intergenerational financial transfers have a positive effect on the old people’s physical health, no linear relationship exists between them. Intergenerational financial transfers are clearly less effective for low-income old people’s physical health than those of middle-income, while the effect on high-income old people’s health is the most insignificant. Studies concerning the effect of intergenerational financial transfers on the elders’ health in developing countries remain limited. Findings of this paper provided great insights into how intergenerational transfers, such as intergenerational financial transfers, may affect the well-beings of old residents in rural areas. Additionally, this study can offer inspiration to policy makers regarding what measures they should take to enhance rural old residents’ well-beings.